PENGARUH KECERDASAN EMOSIONAL TERHADAP PRESTASI BELAJAR PAI SISWA SMP DI JOMBANG - Zuliani, Siti; Aini, Qurrotul; Lailiyah, Nurul (ILJ: Islamic Learning Journal, 2023)
Emotional intelligence is a person's ability to recognize himself, control himself, motivate himself, empathize, and the ability to build relationships (cooperation) with others. Most teachers only consider students to excel if their intelligence scores are high, even though emotional intelligence influences success more. With good emotional intelligence, it is hoped that it can influence student achievement in PAI learning. The method used in this research is a quantitative survey method. With Linear Regression analysis technique. The sample of this research is the students of the one-roof SMPN Pengampon Kabuh Jombang with the results of the general simple linear regression equation: Y = a + bX. Y = 55.461 + 0.429X this equation can be translated: a constanta of 55.461 and a regression coefficient of X of 0.429 states that the regression coefficient is positive, so it can be said that the direction of the influence of variable X is positive. And seen from the r2 value of 0.472 or 47.2%, the amount of contribution (contribution) of intelligence to learning achievement in PAI and 52.8% is influenced by other factors.